Incorporating environmental and sustainability considerations into health technology assessment and clinical and public health guidelines: a scoping review - Pinho-Gomes, Ana-Catarina; Yoo, Seo-Hyun; Allen, Alexander; Maiden, Hannah; Shah, Koonal; Toolan, Michael (International journal of technology assessment in health care, 2022)
Healthcare systems account for a substantial proportion of global carbon emissions and contribute to wider environmental degradation. This scoping review aimed to summarize the evidence currently available on incorporation of environmental and sustainability considerations into health technology assessments (HTAs) and guidelines to support the National In stitute for Health and Care Excellence and analogous bodies in other jurisdictions developing theirown methods and processes. Overall, 7,653 articles were identified, of which 24 were included in this review and split into three key areas – HTA (10 studies), healthcare guidelines (4 studies), and food and dietary guidelines (10 studies). Methodological reviews discussed the pros and cons of different approaches to integrate environmental considerations into HTAs, including adjustments to conventional cost-utility analysis (CUA), cost–benefit analysis, and multicriteria decision analysis. The case studies illustrated the challenges of putting this into practice, such as lack of disaggregated data to evaluate the impact of single technologies and difficulty in conducting thorough life cycle assessments that consider the full environmental effects. Evidence was scant on the incorporation of environmental impacts in clinical practice and public health guidelines. Food and dietary guidelines used adapted CUA based on life cycle assessments, simulation modeling, and qualitative judgments made by expert panels. There is uncertainty on how HTA and guideline committees will handle trade-offs between health and environment, especially when balancing environmental harms that fall largely on society with health benefits for individuals. Further research is warranted to enable integration of environmental considerations into HTA and clinical and public health guidelines.